DIELECTRIC SPECTROSCOPY OF CASING THERMOSETTING COMPOSITE ELECTRICAL INSULATION SYSTEM OF INDUCTION TRACTION ELECTRIC MACHINES - G. V. Bezprozvannych (National Technical University "Kharkiv Polytechnic Institute", 2018)
Introduction. Thermosetting composite electric insulation of traction electric motors undergoes significant heating, moisture, overvoltage, vibration. Purpose. The substantiation of the possibility of using dielectric spectroscopy for monitoring the state of the hull thermosetting composite electric insulating system of induction traction motors (ITM) at the technological stage of manufacturing.. Methodology. In the induction traction motors in which the phases of the stator winding are connected to a «star» and do not have a zero point output, in the case of a two-electrode connection of one of the phases and the housing, the combined characteristics of the capacitance and the dielectric loss tangent of the three-phase hull insulation system are measured. Practical value. It is established that at the second resonant frequency near 10 kHz, the tangent of the dielectric loss is the most sensitive to the state of the composite ITM insulation. Dielectric spectroscopy at alternating voltage of the combined dielectric characteristics makes it possible to evaluate the state of the hull thermosetting electrical insulating system at the final stage of manufacturing of induction traction motors.